THE CONCEPT OF INSAN KAMIL AL-JILI AND ITS RELEVANCE TO SOCIAL SOCIETY TASAWUF SCIENCE PERSPECTIVE: Indonesia - Abdillah, Muhammad Hanif; Khudori Soleh, Achmad (Kopertais Wilayah III Yogyakarta, 2023)
Social change in people's lives is something that cannot be avoided. As a human being who is always adaptive to developments over time, it is a challenge to continue to strengthen our faith when the temptations of technology become more intense. Society is a macro part of various micro elements within it, namely humans with various personalities. To create a harmonious society will really depend on individuals in society as a whole, so the concept of insan kamil Al-Jili is a good way to make this happen. The method in this research uses a qualitative approach with library research methods, where researchers will collect various data through library sources such as books and journals. The aim of this research is to explain the concept of insan kamil Al-Jili and its relevance to social society. The results of this research are that the concept of insan kamil Al-Jili can be concluded with several points about strengthening individuals which will have an impact on social culture, including: 1) Islam is a system that provides guidance and broad benefits for individuals and society 2) the important role of faith in directs a Muslim's beliefs and behavior, and how this can impact their quality of life in modern society 3) worship is not only a spiritual aspect, but also has a significant impact on the holistic development of individuals and their contribution to the formation of positive values in society 4 ) the importance of Ihsan's attitude in interacting with Allah and fellow humans 5) the importance of love for Allah as a foundation for good moral and ethical behavior in interacting with God and fellow humans, apart from that love for Allah can have a positive impact in various aspects of life, such as morals and consistency in the values adhered to 6) the importance of spiritual search and a deep understanding of God in individual development, as well as education in religious values and positive morals 7) the role of human beings in maintaining balance in the universe and society. Keywords: Tasawuf; Al-Jili; Insan Kamil; Social.